Characteristics of vegetation carbon sink carrying capacity and restoration potential of China in recent 40 years - Wu, Luhua; Zhang, Yun; Luo, Guangjie; Chen, Dan; Yang, Dongni; Yang, Yifan; Tian, Fengxia (Frontiers in Forests and Global Change, 2023)
Improving vegetation carbon sink is a key measure for China to achieve the goal of carbon neutrality. However, the gradual saturation of vegetation carbon fixation under the constraints of climate change and human activities has limited the long-term and sustainable growth of vegetation carbon sinks, resulting in significant uncertainty in understanding future carbon sink capacity and recovery potential. In this study, NPP has been selected as a carbon sink indicator to quantitatively evaluated the carbon sink carrying capacity (CSCC) and the carbon sink resilience (CSR) of China. Results demonstrates that (1) the NPP of vegetation cover areas in China exhibited an increasing trend from 1981 to 2018, with an average growth rate of 1.66 g C m-2 yr-1 and a total net NPP increase of 0.32 P g C. (2) The average CSCC in China was 658.59 g C m-2 yr-1, with a total amount of 4.13 Pg C yr-1. The NPP exceeded 60% of CSCC in various years, and the total NPP in 2018 was 3.26 Pg C yr-1, which reached 78.74% of CSCC. In the future, carbon sink that can be increased is 0.88 Pg C yr-1, with an increase proportion of 21.26%. (3) From 2000 to 2018, the NPP of vegetation-covered area (VCA) in China had generally maintained a positive succession trend with the stronger CSR. Only four provinces (HUN, CQ, AH, and JS) in China have showed the extremely strong levels of CSR. The study has revealed the huge and sustainable CSCC and restoration potential in China over the past 40 years, and provided spatial positioning and theoretical guidance for future ecological carbon sink restoration and benefit assessment.